When a health policy cuts both ways: Impact of the National Emergency Access Target policy on staff and emergency department performance. (8th October 2019) - Forero, Roberto; Man, Nicola; Nahidi, Shizar; Fitzgerald, Gerard; Fatovich, Daniel; Mohsin, Mohammed; Ngo, Hanh; Toloo, Ghasem (Sam); Gibson, Nick; McCarthy, Sally; Mountain, David; Hillman, Ken; et al.
Abstract: Objective: To explore the impact of the Four‐Hour Rule/National Emergency Access Target (4HR/NEAT) on staff and ED performance. Methods: A mixed‐methods study design was used to link performance data from 16 participating hospitals with the experiences reported by 119 ED staff during policy implementation. Quantitative and qualitative measures were triangulated to identify the staff and organisational effects on hospital performance. An overall score was developed to categorise hospitals into: high, moderate and low performers, then compared with four qualitative themes: social factors, ED management, ED outcomes and 4HR/NEAT compliance. Results: Key factors identified were stress and morale; intergroup dynamics; interaction with patients; resource management; education and training; financial incentives; impact on quality and safety; perceived improvements on access block and overcrowding. High performing hospitals reported increased stress and decreased morale, decreased staff–patient communication and staff shortages; significant changes in ED management and effective use of the whole‐of‐hospital approach. Moderate performing hospitals reported similar characteristics to a lesser degree, and the perception that 4HR/NEAT did not impact ED practice. Low performing hospitals also reported increased stress and low morale and a less effective whole‐of‐hospital approach. ED staff also reported a reduction in communication with patients. Conclusions: There was strong evidence of an association between high stress and low morale and the implementation of the 4HR/NEAT across all levels of performance. These adverse consequences of the 4HR/NEAT implementation indicate that a more nuanced approach to efficiency improvements is required. This would balance processes measured by 4HR/NEAT against a range of other clinical and organisational performance measures.